Preparation of a textile and clothing company to lean implementation by identifying ergonomic and environmental risks - Maia, Laura Costa (2013)
This paper intends to identify ergonomic and environmental risks, in the different sectors of the Portuguese Textile and Clothing Industry (TCI). This identification will be used in order to have a better understanding of the risks in each sector of TCI. Knowing these risks, some more focused proposals oriented by a Lean methodology, could be recommended to eliminate them more rapidly. The Lean methodology to implement Lean in TCI is already in development and includes ergonomic and sustainable tools to solve the problems related with the identified risks. These tools will allow analysing and evaluating the risks to improve the work environment.